Effect of long‐term organic and mineral fertilization strategies on rhizosphere microbiota assemblage and performance of lettuce. (29th April 2019) - Paul Chowdhury, Soumitra; Babin, Doreen; Sandmann, Martin; Jacquiod, Samuel; Sommermann, Loreen; Sørensen, Søren Johannes; Fliessbach, Andreas; Mäder, Paul; Geistlinger, Joerg; Smalla, Kornelia; Rothballer, Michael; Grosch, Rita
Summary: Long‐term agricultural fertilization strategies gradually change soil properties including the associated microbial communities. Cultivated crops recruit beneficial microbes from the surrounding soil environment via root exudates. In this study, we aimed to investigate the effects of long‐term fertilization strategies across field sites on the rhizosphere prokaryotic ( Bacteria and Archaea ) community composition and plant performance. We conducted growth chamber experiments with lettuce ( Lactuca sativa L.) cultivated in soils from two long‐term field experiments, each of which compared organic versus mineral fertilization strategies. 16S rRNA gene amplicon sequencing revealed the assemblage of a rhizosphere core microbiota shared in all lettuce plants across soils, going beyond differences in community composition depending on field site and fertilization strategies. The enhanced expression of several plant genes with roles in oxidative and biotic stress signalling pathways in lettuce grown in soils with organic indicates an induced physiological status in plants. Lettuce plants grown in soils with different fertilization histories were visibly free of stress symptoms and achieved comparable biomass. This suggests a positive aboveground plant response to belowground plant–microbe interactions in the rhizosphere. Besides effects of fertilization strategy and field site, our results demonstrate the crucial role of the plant in driving rhizosphere microbiota assemblage.